2023
DOI: 10.21091/mppa.2023.2010
|View full text |Cite
|
Sign up to set email alerts
|

Pain Catastrophizing in Dance Students in Relation to Resilient Behavior and Self-Reported Injuries

Abstract: AIMS: Pain catastrophizing is characterized by a set of negative emotional and cognitive processes in response to pain, with a tendency to focus inordinately on the painful sensation, exaggerate the damage, and perceive feelings of helplessness. It is a psychological factor that can be treated to help people more effectively cope with pain. In this cross-sectional study, we explored the relationship between self-reported injuries, resilient behavior, and pain catastrophizing in dance students, with more than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Early studies on animal muscles 32 have indicated that eccentric training provides an essential mechanical stimulus for amplifying the number of rat muscle fibers after downhill running 33 36 . This increase in the number of serially connected muscle fibers encourages faster contraction speed and increased muscle strength during muscle contraction 37 , 38 . Chronic eccentric training appears to be associated with modifications in the length-tension curve of muscles 39 , 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Early studies on animal muscles 32 have indicated that eccentric training provides an essential mechanical stimulus for amplifying the number of rat muscle fibers after downhill running 33 36 . This increase in the number of serially connected muscle fibers encourages faster contraction speed and increased muscle strength during muscle contraction 37 , 38 . Chronic eccentric training appears to be associated with modifications in the length-tension curve of muscles 39 , 40 .…”
Section: Discussionmentioning
confidence: 99%